1990
DOI: 10.1111/j.1467-9280.1990.tb00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, Social Class, and Antisocial Behavior in a Sample of 4,462 Men

Abstract: Two hypotheses have been offered to explain the relation between testosterone and antisocial behavior in delinquent and criminal populations. One is that testosterone leads directly to antisocial behavior. The other is that a constellation of dominance, competitiveness, and sensation seeking associated with testosterone leads to either antisocial or prosocial behavior, depending upon an individual's resources and background. Analysis of archival data from 4,462 U.S. military veterans supported the first hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
139
2
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(148 citation statements)
references
References 10 publications
4
139
2
3
Order By: Relevance
“…Although we did not measure the behavioral or physical pathways linking T with mating success in this analysis, T has previously been shown to bolster traits related to mating effort and attractiveness, such as musculature (1,28,29), motivation to win during competition (30), and pursuit of social dominance (2,31). Men with higher T have also been shown to have physical attributes deemed attractive by females and to have more recent and lifetime sexual partners (32)(33)(34). Although families traditionally played a primary role in arranging courtship and marriage in the Philippines, courting in recent decades has gradually moved toward males and females meeting independent of familial control (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we did not measure the behavioral or physical pathways linking T with mating success in this analysis, T has previously been shown to bolster traits related to mating effort and attractiveness, such as musculature (1,28,29), motivation to win during competition (30), and pursuit of social dominance (2,31). Men with higher T have also been shown to have physical attributes deemed attractive by females and to have more recent and lifetime sexual partners (32)(33)(34). Although families traditionally played a primary role in arranging courtship and marriage in the Philippines, courting in recent decades has gradually moved toward males and females meeting independent of familial control (35).…”
Section: Discussionmentioning
confidence: 99%
“…Although helpful in securing mates, many T-stimulated behaviors may conflict with partnership stability and parenting (4,33). Indeed, men with higher T have been shown to be more likely to have marital problems and to be divorced (4,18), whereas men with lower T have been found to spend more time with their wives (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, both men and women use prosocial strategies to attain status (Anderson and Kilduff 2009;Cheng et al 2012;Hawley 1999), studies that demonstrate a positive relationship between T and antisocial behavior have been mostly conducted with men (e.g. Dabbs and Morris 1990;for review, Archer 2006) and studies that demonstrate a positive relationship between T and prosocial behavior have been mostly conducted with women (e.g., Boskem et al 2013;Eisenegger et al 2010;van Honk et al 2012) -a bias that may inappropriately lead researchers to predict a sex difference. The present study was conducted with women.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies suggest that, at least in certain contexts, T influences prosocial behavior in women. For men, although some studies have found a link between T administration and behaviors such as reduced lying (Wibral et al 2012), there is less empirical evidence to support a hypothesized relationship between T and prosocial behavior (e.g., Dabbs and Morris 1990).…”
Section: Introductionmentioning
confidence: 98%